2016
DOI: 10.1088/0253-6102/65/6/671
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Behavior of Solution in Integrable Nonlocal Lakshmanan—Porsezian—Daniel Equation

Abstract: The integrable nonlocal Lakshmanan—Porsezian—Daniel (LPD) equation which has the higher-order terms (dispersions and nonlinear effects) is first introduced. We demonstrate the integrability of the nonlocal LPD equation, provide its Lax pair, and present its rational soliton solutions and self-potential function by using the degenerate Darboux transformation. From the numerical plots of solutions, the compression effects of the real refractive index profile and the gain-or-loss distribution produced by δ are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…THEOREM 2. The nonlocal DSII equation possesses two N th-order rational solutions A and Q given by (34) with the two following polynomials f and g:…”
Section: Rational Solutions Of the Nonlocal Dsii Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…THEOREM 2. The nonlocal DSII equation possesses two N th-order rational solutions A and Q given by (34) with the two following polynomials f and g:…”
Section: Rational Solutions Of the Nonlocal Dsii Equationmentioning
confidence: 99%
“…Note that two types of rogue wave solutions for the nonlocal DSI equation were obtained formally in [22], and Darboux transformations and global explicit solutions for the x-nonlocal DSI equation were given in [23]. Besides, a lot of work was done after that for these equations and other nonlocal equations [19,20,[23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Since the LDP model plays a significant role in portraying several complex phenomena, many authors find and analysed the solution using analytical as well as numerical schemes. For instance, Arshed et al 54 find the optical solitons for the considered model with the help of exp-(ϕ(ξ))-expansion method in birefringent fibres; the bright optical solitons have been illustrated by Alqahtani et al 55 for LPD model using semi-inverse variational principle, the group invariant solutions, and optical solitons in optical fibres; and PCF is presented by Bansal et al, 56 the optical solitons in birefringent fibres for the considered model achieved by Ekici 57 using the extended Jacobi's elliptic function expansion method; Guzman et al 58 applied the method of undetermined coefficients in order to find the optical solitons with polarization mode dispersion for the considered complex non-linear problem; the singular and dark optical solitons are obtained by Javid and Raza 59 ; singular and dark optical solitons have been obtained by Jawad et al 60 ; and many others [61][62][63][64] presented some interesting results. However, these techniques have their one limitation like huge computation, perturbation, and discretization.…”
Section: Introductionmentioning
confidence: 99%
“…[20,29,33]. The integrable nonlocal LPD equation whose the potential functions satisfy r(x, t) = q * (−x, t) is studied via Darboux transformation in [21]. The authors demonstrated the integrability of the nonlocal LPD equation, provided its Lax pair, and presented its rational soliton solutions and self-potential function.…”
mentioning
confidence: 99%